Biosocial Criminology: History, Theory, Research Evidence, and Policy - Bedoya, AnaCristina (Victims & offenders, 2023)
Biological perspectives on criminology were widely accepted in the United States in the late 1800s to early 1900s, but quickly fell out of favor due to eugenicists in the field misusing research and sociocriminologists outside of the field vilifying this avenue of investigation. In recent years, the field has rebounded. This review provides a detailed history of biosocial criminology, exploring its development alongside sociocriminology with a focus on the social and personal histories that contributed to the resurgence of biosocial criminology. A brief and selective literature review follows, providing a general overview of methodologies used in the field, key findings, and policy and practice implications. We conclude by discussing the utility of the biosocial perspective in criminology for studying offending and victimization. We also discuss challenges of applying biosocial research to policy and practice, as well as next steps for the field.